A new species of genus Aplosonyx Chevrolat (Coleoptera: Chrysomelidae: Galerucinae) from China, with a key to the Chinese known species - Zhang, Lijie; Li, Wenzhu; Zhang, Yalin; Yang, Xingke (Zootaxa, 2008)
A new species, Aplosonyx metallicus Chen from Sichuan Province is described. A. pictus omeiensis is resurrected from synonymy with A. pictus and elevated to species. Both A. pictus and A. omeiensis are transferred from Sphenoraia back to the genus Aplosonyx. And a key to the Chinese species is provided.